2002
DOI: 10.2166/wst.2002.0145
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient distribution in the Bosphorus and surrounding areas

Abstract: As part of a five years monitoring project "Water Quality Monitoring of the Strait of Istanbul", February-December 1999 nutrient dynamics of the Black Sea-the Sea of Marmara transect are studied to evaluate the effect of discharges given by deep disposals. Through a one-year study, upper layer nutrient concentrations were generally under the effect of northwestern-shelf Black Sea originated waters. This effect was strictly observed in July, when the upper layer flow was the thickest. On the other hand, partly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Decarbonization plants and advanced biological treatment facilities do exist; however, they are in the minority (Maryam and Büyükgüngör, 2017). Many studies have shown that this "deep discharge" practice has caused an excess of the nutrient load that exceeds the capacity of the Marmara's marine ecosystem (Okuş et al, 2002;Taş et al, 2016;Çardak et al, 2015). Number and type of wastewater treatment plants in the region are given in the Table 2.…”
Section: Mucilage Phenomenon In the Sea Of Marmaramentioning
confidence: 99%
“…Decarbonization plants and advanced biological treatment facilities do exist; however, they are in the minority (Maryam and Büyükgüngör, 2017). Many studies have shown that this "deep discharge" practice has caused an excess of the nutrient load that exceeds the capacity of the Marmara's marine ecosystem (Okuş et al, 2002;Taş et al, 2016;Çardak et al, 2015). Number and type of wastewater treatment plants in the region are given in the Table 2.…”
Section: Mucilage Phenomenon In the Sea Of Marmaramentioning
confidence: 99%
“…Additionally, Orhon et al (2021) argue that the Black Sea Current in the Bosphorus Strait discharges highly polluted water bodies from the Black Sea into the Marmara Sea. Thus, the nutrient load of the Marmara Sea exceeds the capacity of the Marmara's marine ecosystem (Okuş et al,2002;Taş et al, 2016;Çardak et al, 2015) and results in environmental disasters such as mucilage (Savun-Hekimoğlu and Gazioğlu, 2021).…”
Section: Introductionmentioning
confidence: 99%